Manajemen Perwasitan Asosiasi Futsal Kabupaten Kebumen Tahun 2020 (Universitas Negeri Semarang, 2020)
The object of this study is to find out how the management of referee’s, human resources, and achievements of referees in Kebumen Regency. The reasercher used qualitative method. Research collection data the method of observation, interviews, and documentation. The subject of this research official and referee’s members. Data analysis technique used the method triangulation technique data. Data analysis techniques include data collection, data reduction, data presentation and drawing data conclusion. The results of this study showed that 1) futsal referees organization palnning has been going well;2) the organization runs well;3) the mobilization by the management has not fully gone well, on this physical development program that has no been cariried out rou tirely;4) supervision goes to well;5) human resources in terms of making judgment is still low;6) AFK Kebumen’s referee performance is quite good. . From the result of this study, it could be concluded that management of AFK referee’s in Kebumen Regency was optimal in terms of planning more improved of comunication, refresher physical referees, and increase the desclipline of referees when on duty as well as the achievements of referees to promote it to a higher level.